Final answer:
To convert the given equation y + 4 = 1.5(x + 2) to standard form, distribute the 1.5, rearrange terms and multiply by -1 to get the final standard form equation 1.5x - y = 1.
Step-by-step explanation:
To write the given equation y + 4 = 1.5(x + 2) in standard form, we want to express it in the form Ax + By = C, where A, B, and C are constants. First, we distribute the 1.5 across the (x + 2):
y + 4 = 1.5x + 3.
Now, we subtract 4 from both sides to isolate y on the left side:
y = 1.5x - 1.
To get it into standard form, we subtract 1.5x from both sides:
-1.5x + y = -1.
This is now in standard form, and we typically want the x coefficient to be positive. Therefore, we can multiply the entire equation by -1:
1.5x - y = 1
The standard form equation